PENGARUH LATIHAN BALLHANDLING TERHADAP KETERAMPILAN MENGGIRING BOLA (DRIBBLING) PADA PEMAIN BOLA BASKET TIM CHICKEN SOUP PEKANBARU - Ihsan, Meiza; ', Ramadi; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Issues raised in this research is that the dribbling skills down yet so good. This is evident from some of the matches have been followed as in the basketball game between clubs in Pekanbaru, as well as in test matches against other clubs in Pekanbaru. Chicken Soup basketball team Pekanbaru when dribbling is not so optimal, such as often loses control of the ball when dribbling to carry out attacks and often find it difficult to pass an opponent because of a lack of skills in dribbling. This research is an experimental treatment (Experimental), the population in this research is a team of basketball players of Chicken Soup Pekanbaru. The sample in this research is a population which numbered 15 people. The Data collection techniques in the can from the pre-test and post-test. The instruments used in this research is the Dribble Control Test, which aims to measure the skills of dribbling. As the independent variable is ballhandling drills (X), while the dependent variable is dribbling skills (dribbling) (Y). After that, the data is processed with statistical, normality test with Liliefors test at significant level 0,05α. Data from normal distribution with Lhitung pree-test 0.1199 and Ltabel 0.220, while post-test Lhitung 0.1320 and Ltabel 0.220. The Hypothesis is contained ballhandling drills influence on dribbling skills (dribbling). Based on t test analysis produces Thitung of 24.32 and 1,761 Ttabel means Thitung> Ttabel. It can be concluded that Ha is accepted, it can be concluded that there is a significant effect of ballhandling drills toward dribbling skills (dribbling) in the basketball players team of Chicken Soup Pekanbaru. Key Words : Ballhandling drills, dribbling, basketball